Psychographic Profiling of Skincare Indonesian Consumers: A Multidimensional Segmentation Approach - Suryaneta Suryaneta; Andhyka Tyaz Nugraha; Tri Noviantoro; Nisa Novia Avien Christy; M.Raihan Huzhaifi Muslim (Media Ekonomi dan Manajemen, 2026)
This study assesses whether a multidimensional psychographic base that joins values, life visions, aesthetic styles, and media preferences can explain skincare consumer behavior in Indonesia and translate directly into brand decisions. A cross sectional online survey of two hundred seventy consumers employed seven-point scales for twelve value items, ten life vision items, nine aesthetic style items, and nine media preference items. The instrument showed satisfactory internal consistency with Cronbach’s alpha of 0.81 for values, 0.78 for life visions, 0.85 for aesthetic styles, and 0.78 for media preferences. Dimensionality was examined with principal components at the block level and audience segments were identified with Gaussian mixture models, with the number of classes selected by the Bayesian Information Criterion. The analysis yielded six interpretable segments. Values place holistic health, emotional balance, and environmental or ethical responsibility at the center of decision making. Aesthetic attraction is strongest for modern minimalism followed by classic and sporty codes, while luxury and futuristic codes are less salient. Media use concentrates on Instagram and TikTok with e-commerce and YouTube as important complements. These findings establish a direct bridge from latent motives to actionable levers by pairing claims and design languages with the media habitats in which persuasion occurs. Brand teams can emphasize health and calm narratives with credible testing, employ transparent and minimalist clinical visual systems, and activate creator led short video content with seamless handoff to e-commerce, while using longer instructional content for audiences that prefer YouTube and Facebook. Limitations include a youthful and digital first sample, self-report measures, and a cross sectional design. The study offers an empirically grounded baseline for psychographic profiling in skincare and a practical roadmap for audience in culture strategy that is both differentiated and repeatable.